THE IMPACT OF PSYCHOLOGICAL WORK ENVIRONMENT TOWARDS EMPLOYEE JOB PERFORMANCE IN HOTEL MANAGEMENT - Putri, Ristia Kencana; Garibaldi, Gemala (Emerging Markets : Business and Management Studies Journal, 2016)
It is important to take psychological work environment into a study, due to the fact that hotels sometimes do not aware how important is the role of psychological work environment in affecting employee job performance because it is intangible. However, various researches have confirmed that psychological work environment is able to affect positively to employee job performance. Due to this fact, this research aims to study whether the psychological work environment affects employee job performance and to analyze which psychological work environment gives the biggest impact on employee job performance. Simple/linear regression is used to analyze the relationship between psychological work environment and employee job performance. The data used for this quantitative research is collected by questionnaire distributed to a total of 67 staff level employees in a five-star hotel located in Lippo Village. In conclusion, it is confirmed that psychological work environment affects positively to employee job performance, and job attitude gives the biggest impact on employee job performance. The studied company is suggested to improve psychological work environment, particularly job attitude gives the biggest impact.